2012
DOI: 10.1016/j.jcmg.2011.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Arterial FDG Uptake and Biomarkers in Peripheral Artery Disease

Abstract: OBJECTIVES A prospective, multicenter 18fluorine-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT) imaging study was performed to estimate the correlations among arterial FDG uptake and atherosclerotic plaque biomarkers in patients with peripheral artery disease. BACKGROUND Inflammation within atherosclerotic plaques is associated with instability of the plaque and future cardiovascular events. Previous studies have shown that 18F-FDG-PET/CT is able to quantify inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 16 publications
1
73
0
2
Order By: Relevance
“…However, clinical and experimental studies have failed to show a correlation between 18 F-FDG uptake and macrophage content in atherosclerotic lesions. 21, 26 The evidence suggests that the presence of macrophages does not always indicate active inflammation. Recent studies have revealed macrophage heterogeneity in atherosclerotic lesions, 27 and approximately 25% of macrophages in coronary atherosclerotic plaques have an antiinflammatory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical and experimental studies have failed to show a correlation between 18 F-FDG uptake and macrophage content in atherosclerotic lesions. 21, 26 The evidence suggests that the presence of macrophages does not always indicate active inflammation. Recent studies have revealed macrophage heterogeneity in atherosclerotic lesions, 27 and approximately 25% of macrophages in coronary atherosclerotic plaques have an antiinflammatory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Early 18 F-FDG–based PET imaging studies showed promising results in both the detection of inflammatory lesions and the response of these lesions to therapeutic interventions (48). However, some clinical studies failed to demonstrate a significant association between plaque inflammation and 18 F-FDG uptake (4,9), hindering the translation of experimental studies to the clinical practice. Additionally, a direct association between increased glucose uptake and specific macrophage functions or activation states has yet to be validated.…”
mentioning
confidence: 99%
“…Thus, an increase in infl ammatory cells in the perivascular adipose tissue, the largest endocrine organ, does not play a role only in atherogenesis, but it may also infl uence imaging results. Simple correlations of FDG uptake with risk factors, including already existing diseases such as metabolic syndrome, diabetes mellitus as well as with certain laboratory markers of atherosclerosis such as CRP [24,25,26], malondialdehyde-modifi ed LDL [27], LDL-cholesterol and leptin [28], and matrix metalloproteinases [29] were not helpful at all. Interestingly, in particular in peripheral arterial disease, there was no correlation between F-18-FDG uptake and various biomarkers, including hsCRP.…”
Section: F-18-fl Uorodeoxyglucose (F-18-fdg)mentioning
confidence: 99%